A Retrospective Contrast of Artificial and Human Intelligence in Brain Tumor Classification (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The Central Nervous System comprising of brain and spinal cord responsible for your everyday activity, from your cognitive function, memory, thinking, speaking, maintaining hemostasis, to reflex actions are controlled here. Basically, a small damage to your brain may shake the normal rhythm of life. This is a retrospective description that has observation of 10 different brain tumor patients from the Republican Hospital of Samarkand, 2025 outline. In the collection of patient cases of brain tumors, there are 10% pediatric cases, 20% from age range (20-60) and 60% from age range (50-80). Discussion: In this retrospective discussion, the study is dependent on completeness of data records, and it is extracted from single center, with no direct applications of AI, for only comparisons are made. Conclusion. This study highlights manual staging if tumor that remains vital and it’s limitations are inherent with emerging AI technologies, hence global health being the major impact.